Low voltage and large current DC superconducting power cable designs for 10 km to 100km transmission line using experimental data of Ishikari project. (September 2019) - Yamaguchi, Satarou; Yamada, Takeo; Iitsuka, Takashi; Sato, Akio; Sawamura, Toru; Sytnikov, Victor
Abstract: Main merit of the DC superconducting power transmission line is low loss even in low voltage power transmission. It should be realized when the transmission length is long. Therefore, we discuss and analyse an aspect of thermo-hydrodynamic performance of Ishikari project, and show one design of 100 km transmission line. At the same time, we also discuss the cable design and the rated voltage of the cable is lower than 50 kV for 500MW transmission. This is one of the most important advantages to make the DC power grid because we can omit an ultra-high voltage substation, the primary and the secondary substations and we can connect the power stations to the distribution stations directly. Finally, we may be able to reduce the construction and operation costs of the power grid.